KAJIAN SIFAT EKOFISIOLOGI TIGA JENIS GULMA DI BAWAH NAUNGAN STUDY OF ECOPHYSIOLOGICAL CHARACTERISTICS ON THREE SPECIES OF WEED UNDER SHADE - , Mahfudz (Pembangunan Pedesaan, 2006)
This research aimed at analyzing morphological, anatomical and physiological changes in weeds in relation to their adaptation to low intensity light. Research was designed in a Split plot Design. The main plot was level of shade consisted of two levels, i.e., without shade and 50% shade. The subplot was three species of chosen weed, i.e., Bidens pilosa, Paspalum conjugatum, and Cuphea balsamona. Result of the research showed that P. canjugatum, B. pilosa, and C. balsamona were significantly different in their adaptation to shade. P. conjugatum was more tolerant to shade compared to B. pilosa and C. balsamona. Under 50% shades, P. conjugatum grow faster, utilized more N efficiently, and produced seed relatively similar to the condition without shade. P. conjugatum was a competitive weed under shade condition. B. pilosa, on the other hand, was competitive under condition without shade.